Isolation And Characterisation Of Chemical Constituents With Anti-Methicilin Resistant Staphylococcus Aureus Activity From Mesua Ferrea Leaf Extract - Alagasamy, Sangeeta Vani (2018)
The present study aims to isolate compounds with antimicrobial activity from Mesua ferrea leaf employing bioassay guided approach. An antibacterial assay guided extraction and compound isolation procedure was carried out on Mesua ferrea methanolic leaf extract with a number of Gram positives and negatives bacteria. Firstly, M. ferrea leaf extraction technique was optimized using antimicrobial assay guided method. Powdered freeze dried leaves of M. ferrea (particle size 0.5mm) (1:15w/v) using ultrasonic-assisted technique yielded methanol crude extract with a good antibacterial activity against Staphylococcus aureus, MRSA, Pseudomonas aeruginosa, Bacillus subtilis and Escherichia coli.